2020
DOI: 10.1021/acsami.9b23345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Control of Charge Transport Anisotropy in Highly Oriented Friction-Transferred Polythiophene Thin Films

Abstract: Highly oriented thin films of poly[2,5-bis(3-tetradecylthiophen-2-yl)thieno [3,2-b]thiophene] (PBTTT) were prepared by friction-transfer technique followed by their characterization using polarized absorption spectroscopy, angle-dependent polarized Raman spectroscopy, and X-ray diffraction (XRD) techniques. Orientation in high-molecular-weight (M W ) polymers is hampered by chain folding or entanglements, which limit their macromolecular orientation. Interestingly, utilizing high-molecular-weight PBTTT (M W > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…20,28 Charge transport anisotropy in edge-on oriented films generally lies in one order of magnitude due to the presence of conjugated backbones and π−π staking in-plane of the substrate compared to face-on-oriented films. 25,42,43 In-plane charge transport property of the films was probed by fabricating OFETs in each region. Since the orientation direction in different regions was already known, the OFET's channel direction was tuned considering 0°in parallel to the orientation direction of the center region and was set as a reference in each region, as shown in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20,28 Charge transport anisotropy in edge-on oriented films generally lies in one order of magnitude due to the presence of conjugated backbones and π−π staking in-plane of the substrate compared to face-on-oriented films. 25,42,43 In-plane charge transport property of the films was probed by fabricating OFETs in each region. Since the orientation direction in different regions was already known, the OFET's channel direction was tuned considering 0°in parallel to the orientation direction of the center region and was set as a reference in each region, as shown in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
“…GIXD measurements were performed with a Rigaku smart lab X-ray diffractometer with Cu Kα radiation (1.5418 Å) operated at 45 kV (200 mA), as reported in the literature. , A UV–vis–NIR spectrophotometer (JASCO V-770DS) equipped with a polarizer was used to measure the polarized absorption spectra. Thickness measurement and surface topography were measured via an atomic force microscope (AFM) using an SPM-9600 Shimadzu, Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugated polymers are an interesting class of materials due to their versatile and readily tunable semiconducting properties that have made them promising candidate materials for use in flexible electronics, [1][2][3] large-area and/or semitransparent solar cells, [4,5] novel room-temperature thermoelectric generators, [6,7] and soft bioelectronics systems. [8][9][10] While to date, many applications rely on thin, often ultrathin, films of 200 nm or less, increasingly, demand arises for molecularly ordered bulk structures, both for fundamental studies, e.g., to understand the possible anisotropies in properties due to the macromolecular nature of polymer semiconductors, to emerging applications such as thermoelectrics, [11] sensors, [12][13][14][15] and bio-integrated devices. [16,17] As it is generally challenging to grow single crystals of polymeric materials, and polycrystalline/ semicrystalline thin-film structures typically provide only reliable comparisons of properties in maximum two dimensions Semiconducting mesocrystalline bulk polymer specimens that exhibit nearintrinsic properties using channel-die pressing are demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Such high μ in OFETs have been achieved either via vacuum deposition or by producing single crystals via solution processing; however, nonuniformity in the film morphology leading to device-to-device variation is a big challenge. , On the other hand, CPs offer better solution rheology concomitantly high film uniformity over large areas with high reproducibility . Orienting CPs along the channel direction to increase the charge transport in OFETs has been well documented adopting different methods with major improvements in the past 1 decade reported by various research groups. , In addition to this, the crucial role of macromolecular conformation of CPs in thin films and quality of the semiconductor/dielectric interface on charge transport properties of OFETs so far have also been investigated extensively by different groups. , Typically, to demonstrate the state-of-the-art μ of OFETs, the SiO 2 interface is subjected to hydrophobic treatment, which is an effective approach to enhance the μ by few orders of magnitude, and the same has been reported for CPs. Such increment in μ is generally ascribed to improvement in film crystallinity; moreover, it is also reported that the charge traps at the dielectric/semiconductor interface decreases upon hydrophobic treatment of the SiO 2 surface …”
Section: Introductionmentioning
confidence: 99%